ANALISIS PENGARUH KEBIJAKAN HARGA, PROMOSI, DAN FASILITAS PENDUKUNG TERHADAP KEPUASAN PELANGGAN (Studi Empiris Pada Hotel Pandanaran Semarang) - Linda Kusuma Dewi, 08.05.51.0082; Warumu, Penunjang (Students Journal of Economic and Management, 2012)
The study entitled "Analysis of Policy Pricing, Promotion, and Other Facilities Against Customer Satisfaction (Studies in Pandanaran Hotel on Jl. Pandanaran No.58, Semarang)". This study analyzes the pricing policy (X1), promotion (X2) and support facilities (X3) to customer satisfaction (Y). The population in this study are the customers who use the hotel Pandanaran price, promotion and support facilities provided by the hotel. Determination of the samples was done by using "purposive sampling" and the number of samples taken as many as 100 people. Themodel used is regression analysis linearberganda. Previously, testing the validity and reliability, along with classic ujiasumsi of research data. The research results are: (1) The results of statistical calculations with multiple linear regression analysis can be shown by the regression equation Y = 0.183 + 0.043 X1 + X2 + 0.599 X3 e. From the regression equation is known that the pricing policy, promotion, and support facilities have a positive and significant impact on customer satisfaction. (2) The calculation of the coefficient of determination 0.434 magnitude. This indicates that the pricing policy, promotion, and support facilities are able to explain the variables of customer satisfaction at 43.4%. While the remaining 56.6% is explained by other variables not examined such as customer satisfaction, promotion, support facilities, and more. (3) The hypothesis that has been done in this study were: A) There are positive and significant influence on pricing policy of customer satisfaction. B) There are positive and significant promotion of customer satisfaction. C) There is a significant and positive effect on customer satisfaction rates.Key words: Policy Pricing, Promotion and Facilities Supporters Against Customer satisfaction.